Expression of Early Light-Inducible Proteins in Flag Leaves of Field-Grown Barley. - Humbeck, K. (1994)
Early light-inducible protein (ELIP) mRNA and protein levels were analyzed during maturation and senescence of barley (Hordeum vulgare L.) flag leaves under field conditions. The data clearly demonstrate that ELIP mRNA levels are related to the sunlight intensity before sample collection. Levels of mRNAs encoding both low and high molecular mass ELIPs fluctuate in parallel. Changes in mRNA levels are accompanied by corresponding changes in protein levels except for days when average temperatures are high. Comparison of flag leaves at different stages of development in spring and winter barley varieties suggests that light-stress-regulated ELIP gene expression is independent of the developmental stage of the leaves. Although chlorophyll content, photosystem II (PSII) efficiency, and 32-kD herbicide-binding protein of PSII levels decrease drastically after the onset of senescence, ELIP mRNA and protein still accumulate to high levels on bright days.